Green purchasing of kitchen equipment at Anantara Uluwatu Bali Resort - I Komang Trisna Adi Winata; Ni Ketut Bagiastuti; I Gusti Made Wendri; Elvira Septevany (Journal of Applied Sciences in Travel and Hospitality, 2023)
Green purchasing is a form of implementing selection to buy products by prioritizing environmentally friendly principles. Green purchasing of kitchen equipment is important to help reduce environmental impacts and guarantee the safety, stability, welfare, and quality of life of the present and future generations. This research was conducted at Anantara Uluwatu Bali Resort located on Pemutih Street, Labuan Sait, Uluwatu, Bali. This study aims to determine the implementation of green purchasing in the procurement of kitchen equipment at Anantara Uluwatu Bali Resort which was analyzed using green purchasing indicators developed by Pramesti. The data collection method used is interviews with key informants determined purposively and observation techniques using participant observation. The data analysis method used is the qualitative descriptive analysis technique. The results of this study indicate that Anantara Uluwatu Bali Resort has not implemented green purchasing optimally in the procurement of kitchen equipment. There are several obstacles experienced by the purchasing department, namely not having guidelines for implementing green purchasing, the price of goods is expensive, and the production of goods is still small so it cannot meet the needs of kitchen items. The implication of this research is to advise companies to make Standard Operating Procedures regarding implementing green purchasing and to carry out routine price evaluations for suppliers with environmentally friendly product criteria to get prices that match the company’s budget. In addition, the purchasing department can also make regular observations on goods produced by suppliers with environmentally friendly criteria.